2011
DOI: 10.4061/2011/685713
|View full text |Cite
|
Sign up to set email alerts
|

Canine and Human Dirofilariosis in the Rostov Region (Southern Russia)

Abstract: Epidemiological data on canine and human dirofilariosis in the Rostov Region (Southern Russia) are presented. Prevalence of Dirofilaria spp. infections in 795 autochthonous dogs, assessed by the Knott test, was 20.25%. The highest prevalence was found in Novocherkassk (38.3%) and Rostov-on-Don (18.5%), while prevalences were lower in other points of the region. Prevalence of D. repens was 44.7%, prevalence of D. immitis was 30.3%, and coinfections were observed in 25.0% of the dog population. A case finding st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 6 publications
0
32
0
6
Order By: Relevance
“…In the area surrounding Rostov-onDon (southern Russia), the epidemiological profile has substantially changed over the last decade. In 1997, a prevalence of 30% was reported for D. repens (14), whereas in 2011, 20.25% of dogs were infected with Dirofilaria spp., 44.7% of which were infected with D. repens, 30.3% of which were infected with D. immitis, and 25% of which were coinfected with both species (197). Distribution patterns are also changing in the countries of southern Europe where Dirofilaria spp.…”
Section: Canine Dirofilariasismentioning
confidence: 98%
See 1 more Smart Citation
“…In the area surrounding Rostov-onDon (southern Russia), the epidemiological profile has substantially changed over the last decade. In 1997, a prevalence of 30% was reported for D. repens (14), whereas in 2011, 20.25% of dogs were infected with Dirofilaria spp., 44.7% of which were infected with D. repens, 30.3% of which were infected with D. immitis, and 25% of which were coinfected with both species (197). Distribution patterns are also changing in the countries of southern Europe where Dirofilaria spp.…”
Section: Canine Dirofilariasismentioning
confidence: 98%
“…Each of these approaches provides information on different yet complementary aspects of human infections. The following data are based on previously reported retrospective reviews (103,148,197,226,302,328,391) and on bibliographic searches for recently reported cases. The worldwide distribution of human dirofilariasis, as it is currently known (Fig.…”
Section: Dirofilariasis In Human Hostsmentioning
confidence: 99%
“…Epidemi-ological studies suggest that human dirofilariasis occurs in areas with high rates of canine infection (10,13). Cats may also be infected by D. repens or D. immitis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, data analysis revealed three regions with high levels of dirofilariasis. The Rostovsky region had the highest Dirofilaria infestation rates -242 cases [8,58,59,88,89], Nizhegorodsky region had the second highest -129 cases [58], and Volgogradsky district had the third highest -93 cases [59,90]. Warm climate conditions and high infestation rates of Dirofilaria in mosquitoes and dogs in Rostovsky and Volgogradsky regions contribute to high prevalence rates of human dirofilariasis.…”
Section: Human Dirofilarisismentioning
confidence: 99%
“…Dirofilaria spp. were frequency localised in the ocular area (more than 50% cases) [8,79,81,83,84,88,[89][90][91][92][93][94][95][96][97][98][99][100][101][102] follow head and face [8,81,[88][89][90][91][92]96], upper limbs [8,88,89,92,[96][97][98][99][100], stomach [8,88,89], genitals [8,83,84,88,89,91,106,107], breast and knees [8,67,88,…”
Section: Human Dirofilarisismentioning
confidence: 99%